Investigation of fatal traumatic head injuries - Sehlikoglu, Kerem; Turkoglu, Abdurrahim; Bork, Turgay; Batbas, Muhammet (Turkish Assoc Trauma Emergency Surgery, 2024)
BACKGROUND: Traumatic head injuries (THIs) are one of the major causes of death in forensic cases. The aim of this study was to investigate the characteristics of patients with fatal THIs. METHODS: In this study, a total of 311 patients with fatal THIs, who underwent postmortem examinations and/or autopsies, were retrospectively analyzed. Cases were evaluated based on sex, age group, incident origin, cause of the incident, presence of skull fracture, type of fractured bone (if any), fracture localization and pattern, presence and type of intracranial lesion (if any), and cause of death. RESULTS: Out of the patients, 242 (77.8%) were male and 69 (22.2%) were female. Accidents accounted for 235 (75.6%) of the incidents, with in -vehicle traffic accidents causing 117 (37.6%). In 221 cases (71.1%), intracranial lesions and skull fractures were observed together. The most common fractures were base fractures (171 cases) and temporal bone fractures (153 cases). The rate of intracranial hemorrhage was lower in the adult age group (69.7%) compared to the older age group (92.6%). CONCLUSION: The results obtained in this study indicate that the cause of the incident, type of fracture, presence of skull base fracture, and multiple skull fractures increase the likelihood of fatalities. The occurrence of skull fractures reduces intracranial pressure, thereby decreasing the incidence of intracranial lesions. The development and effective enforcement of road traffic safety policies and regulations will reduce the incidence of fatalities.
Ölümcül travmatik kafa yaralanmalarının incelenmesi
Keywords: Head injuries; intracranial lesions; skull fractures; traffic accidents